Valutazione della ricerca: solo effetti perversi? - Mauro Palumbo; Sergio Scamuzzi; Paola Borgna (Quaderni di Sociologia)
The essay introduces the contributions to the issue and traces the main lines of the debate on the evaluation of research in the universities to which they refer: the expected and achieved advantages, the perverse effects attributed to the evaluation on the quality of scientific production and its publication and on the distribution of resources, methodological and score calculation flaws, the overall governance of the evaluation process. It is noted that these analisis vary in their more general premises and implications between the abolition of evaluation seen as an instrument of arbitrary and/or centralistic control, its modifications that take into account innovations such as open access and more weight of peer review by reducing bibliometric automatisms, the questioning of rewards as the main purpose of evaluation, specific technical and methodological improvements. It concludes by stating that in any case general ethical guidelines of the research are in question.